Diabetic post-covid mucormycosis: A dermatoglyphic prediction - Aradhana Sanga; Rita Kumari; Babita Kujur; Rajiv Ranjan; Ashok Kumar Dubey (Journal of Family Medicine and Primary Care)
Aim: To identify the characteristic pattern/parameter among diabetic post-covid mucormycosis patients which may further help in identifying such susceptible patients in a much earlier course of the disease. Materials and Methods: The study was done with 30 diabetic patients (21 males and 9 females) admitted in RIMS Ranchi during the second wave of Covid-19 for post-covid complications. Palm and fingerprint pattern was taken by ink and pad method to measure the qualitative and quantitative parameters. Result: Diabetic post-covid mucormycosis patients were found to have predominantly whorl pattern in males, loop in females, and C-line pattern absent in 36.6%. Proximal axial triradii with ulnar deviation was 76.6%. All the ridge counts (except ab ridge count of right hand) when compared with hypothesized value were found to be significant with P value (<0.005). None of the three angles measured were found to be significant. Conclusion: All the ridge counts (except ab ridge count of right hand) were found to be a reliable parameter for the diagnosis of diabetic post-covid mucormycosis. ATD angle known to be the most reliable parameter for diagnosis of diabetes mellitus in dermatoglyphics is found to be nonreliable with respect to diabetes post-covid mucormycosis.